Interest, utility, liberty - Christin, Olivier (2020)
This article intends to fill a gap in the historiography of the precedents of the political representation during the Ancien Régime. There are several works on different institution of the Ancien Régime that conducted elections and/or corporative negotiation processes that leaded to voting. For example, there are works on how occasionally elections were conducted for authorities of the Catholic Church, universities and other institutions. However, there is a visible absence of historiographical studies about the negotiation-voting practices and the modern and contemporary election by shareholders. Thus, the article seeks to stimulate reflection on the experiences and challenges in the negotiation and decision-making of joint-stock companies, mining companies, water supply companies, sanitation companies, or even large privileged colonial companies.